Synthesis of New Chelating Phosphines Containing an Aryl Chloride Group - Genoux, Alexandre; DiPrimio, Daniel J.; Tereniak, Stephen J.; Holland, Patrick L. (Synthesis, 2023)
The syntheses of bidentate and tripodal phosphine ligands containing aryl chlorides were achieved in 4 and 7 steps respectively, starting from diethyl malonate.
Keywords: phosphines; aryl chloride; chelating ligands